Whether Modulating the Activity of the Temporalparietal Junction Alters Distribution Decisions within Different Contexts: Evidence from a tDCS Study - Luo, Jun; Chen, Shu; Huang, Daqiang; Ye, Hang; Zheng, Haoli (Frontiers in Psychology, 2017)
Distributive justice concerns how individuals and societies distribute income in a just or equal manner. We aimed to test the roles of social preference in behavioral distributive justice. We thus provide evidence of a causal link between the neural and behavioral results through the application of bilateral transcranial direct current stimulation (tDCS) over the temporoparietal junction (TPJ) of our participants. The participants were found to make fairer distributions within the known position after receiving right anodal/left cathodal tDCS and receiving right cathodal/left anodal tDCS over the TPJ than the participants who received the sham stimulation. Simultaneously, we elicited the participants’ advantage inequity aversion and found that the participants who received right anodal/left cathodal tDCS and who received right cathodal/left anodal tDCS over the TPJ were more averse to advantage inequity. Additionally, the participants’ distributive proportions to the lowest income stratum within the known position were strongly related to their social preference of advantage inequity aversion. Therefore, the present study demonstrated that the modulation of the excitability of the TPJ using tDCS altered the distributive decisions of the participants within the known position, and this effect might be attributable to a change in the individuals’ social preferences.